Association of ultrasound-related interruption during cardiopulmonary resuscitation with adult cardiac arrest outcomes: A video-reviewed retrospective study. (April 2020) - Chou, Eric. H; Wang, Chih-Hung; Monfort, Ralph; Likourezos, Antonios; Wolfshohl, Jon; Lu, Tsung-Chien; Hsieh, Yu-Lin; Haines, Lawrence; Dickman, Eitan; Lin, Judy
Abstract: Objectives: To determine the association of focused transthoracic echocardiography (ECHO) related interruption during cardiopulmonary resuscitation (CPR) with patient outcomes in the Emergency Department (ED). Methods: This was a retrospective, single center, cohort study, conducted in an urban community teaching ED. Eligible study subjects were adult patients in the ED with sustained cardiac arrest. Exclusion criteria include traumatic cardiac arrest and age less than 18. All resuscitations were video recorded and were subsequently reviewed by 2 study investigators. The no-flow time from chest compression interruption was analyzed using video review and separated into ECHO-related and non-ECHO related. Our primary outcome was patient survival to hospital discharge and the secondary outcome was the rate of return of spontaneous circulation (ROSC). Multivariate logistic regression analyses were performed to examine the associations between independent variables and outcomes. Results: From January 2016 to May 2017, a total of 210 patients were included for final analysis. The median total no-flow time observed on video was 99.5 s (IQR: 54.0–160.0 s). Among these, a median of 26.5 s (IQR: 0.0–59.0 s) was ECHO-related and a median of 60.5 s (IQR: 34.0–101.9) was non-ECHO-related. The ECHO-related no-flow time between 77 and 122 s (OR: 7.31, 95 % confidence interval [CI]: 1.59–33.59; p-value = 0.01) and ECHO-related interruption ≦ 2 times (OR: 8.22, 95% CI: 1.51–44.64; p-value = 0.01) were positively associated with survival to hospital discharge. ECHO-related interruption ≦ 2 times (OR: 5.55, 95% CI: 2.44–12.61; p-value < 0.001) was also positively associated with ROSC. Conclusion: Short ECHO-related interruption during CPR was positively associated with ROSC and survival to hospital discharge. While ECHO can be a valuable diagnostic tool during CPR, the no-flow time associated with ECHO should be minimized.